2021
DOI: 10.3390/nu13114121
|View full text |Cite
|
Sign up to set email alerts
|

Do Temporal Eating Patterns Differ in Healthy versus Unhealthy Overweight/Obese Individuals?

Abstract: This study examined whether the temporal patterns of energy and macronutrient intake in early and late eating windows were associated with metabolically healthy obesity (MHO) and metabolically unhealthy obesity (MUO) among non-shift workers. A total of 299 overweight/obese non-shift workers (Age: 40.3 ± 6.9 years; 73.6% women; BMI: 31.7 ± 5.0 kg/m2) were recruited in the Klang Valley area of Malaysia. The biochemical parameters were determined from fasting blood samples, whereas information on dietary intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Another strategy would be to utilize chronic taVNS to suppress food cravings and prevent snacking throughout the day. Preventing snacking in the late evening may be particularly effective for weight loss, because chrono‐nutritional studies have demonstrated that consuming high caloric meals later in the day is associated with obesity (Mazri et al, 2021 ; Okada et al, 2019 ). Even though our findings are encouraging, more research including chronic application of taVNS is needed to address issues such as the optimal stimulation parameters or the timing of stimulation relative to food intake, before chronic taVNS can be developed into a clinical tool to assist obese patients with achieving their weight loss goals.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy would be to utilize chronic taVNS to suppress food cravings and prevent snacking throughout the day. Preventing snacking in the late evening may be particularly effective for weight loss, because chrono‐nutritional studies have demonstrated that consuming high caloric meals later in the day is associated with obesity (Mazri et al, 2021 ; Okada et al, 2019 ). Even though our findings are encouraging, more research including chronic application of taVNS is needed to address issues such as the optimal stimulation parameters or the timing of stimulation relative to food intake, before chronic taVNS can be developed into a clinical tool to assist obese patients with achieving their weight loss goals.…”
Section: Discussionmentioning
confidence: 99%
“…Greater energy intake towards earlier part of the day and smaller intake towards later part of the day is beneficial for both chronotypes [48].…”
Section: Temporal Pattern Of Energy Intakementioning
confidence: 98%
“…In addition, the majority of morning chronotypes did not achieve the 75% energy intake recommendation in the early window. Our recent work shows that the energy intake of 62-64% during the early window has benefits for metabolic health among overweight/obese adults [48]. Therefore, the recommendation was revised to improve compliance and at the same time achieve a significant level of intake towards clinical benefits.…”
Section: Refinement Of the Integrated Chrono-nutrition Weight Reducti...mentioning
confidence: 99%
“…Observational data have revealed that meal regularity and, in particular, high energy intake in the morning is associated with wellbeing outcomes ( 216 ). It is important to note that food timing also influences the metabolic state of obese subjects: as observed by Mazri et al., early temporal patterns of energy and macronutrient intake characterized obesity with healthy metabolic status ( 217 ). In diabetic patients, morning distribution of food intake, especially a carbohydrate-rich breakfast, accelerates weight loss, reduces appetite and craving, and thus improves metabolic parameters, such as postprandial glycemia and glycated hemoglobin ( 218 220 ).…”
Section: Nutrition As Metronome: Circadian Re-synchronizationmentioning
confidence: 99%